Aura's Disappearance and Remolding in the Digital Age: Digital Art's Impact on the Traditional Aesthetic System (Journal of Global Arts Studies, 2025)
Background： Building on Benjamin's The Work of Art in the Age of Mechanical Reproduction, technology (like photography and film) liberated art from ritualistic worship, shifting its focus to display value and political function. The digital age extends this liberation: AI, VR/AR, and other technologies create new art forms, impacting the traditional "aura" and value system. Concurrently, digital art introduces issues of copyright and the digital divide. Objective： Starting with the disappearance of Benjamin's "aura" due to mechanical reproduction, this paper discusses changes in art's creation, dissemination, and reception in the digital age. It analyzes digital art through technology, aesthetics, form, and ethics, revealing technology's impact on traditional art and discussing digital art's interactivity and aesthetic modernity to provide a reference for social development. Methods： Combined with Benjamin and other theories and specific cases, from the technology, experience, ecology, ethics multi-dimensional deconstruction, contrast the artistic characteristics of different times. Results: Digital art reconstructs art noumenon, aesthetic experience and ecology, but it also exposes ethical and practical problems such as copyright dispute, digital divide and market bubble. Conclusion: The "distributed brilliance" of the digital age is not based on material uniqueness, It is reflected in the variability of program generation, the non-replicability of interactive experience, and the value recognition of community consensus. And the "relational truth" given by blockchain technology, it is necessary to balance technology and humanities to promote its healthy development in the future.
Keywords: Digital Art; Aura; Benjamin; Interactivity